Radiation Prophylaxis for Hip Salvage Surgery in Cerebral Palsy: Can We Reduce the Incidence of Heterotopic Ossification?. Issue 5 (May 2019) - Davis, Eric; Williams, Kathryn; Matheney, Travis H.; Snyder, Brian; Marcus, Karen J.; Shore, Benjamin J.
Abstract : Background: Heterotopic ossification (HO) is a well-recognized complication of proximal femoral resection (PFR) surgery in children with cerebral palsy (CP). Although single-dose radiation prophylaxis (SDRP) has been shown to be effective at lowering the rates of HO following adult total hip arthroplasty; there has been limited study examining the efficacy of SDRP for HO prevention in children with CP undergoing PFR. The purpose of this study was to assess the efficacy of SDRP in children with CP undergoing PFR. Methods: This retrospective case control series identified all patients from one tertiary children's hospital undergoing PFHR. Patients were dichotomized into (1) SDRP and (2) non-SDRP groups. In SDRP, radiation was delivered preoperatively at a dose of 7.5 Gy utilizing a 6 MV photon beam. The incidence of HO in the SDRP cohort was compared to historic data using binomial testing. The size of HO lesions was compared using Wilcoxon signed-rank test. McCarthy, Brooker, and Anatomic Classifications of HO were compared using repeated measures logistic regression. Results: Twenty-three patients (mean age, 15.5) and 35 hips (17 SDRP, 18 Non-SDRP) were included in the analysis. There were 17 females and 6 males in the cohort with the majority classified as GMFCS V, 21/23 (91%). HO was seen in 6 of the SDRP cohort (6/17, 35%) and 15 of the non-SDRP cohort (15/18, 83%) ( P =0.015). The average size of HO at maturity was 282.7 mm 2 in the SDRP cohort compared with 1221.5 mm 2 in the Non-SDRP cohort ( P =0.026). Radiation treatment was associated with a 938.9 mm 2 decrease in HO size at maturity ( P = 0.026). Multivariate repeated measures logistic regression analysis found that non-SDRP hips had 13 times higher odds of developing HO ( P =0.015). There were no significant differences in infection rates between the 2 cohorts and there were no radiation-associated complications. Conclusions: Short-term follow up demonstrates that SDRP is a safe and efficacious intervention in decreasing the incidence and size of HO in children with CP undergoing PFR. Levels of Evidence: Level III—Case control cohort study.